DETERMINAN DARI SIKAP DAN MINAT TERHADAP BANK SYARIAH - Abdul Azis Safii (Sekolah Tinggi Ilmu Ekonomi Cendekia Bojonegoro, 2019)
This study aims to examine the factors that influence the adoption of Islamic banking in general in Indonesia. By using primary data collected from a number of 276 respondents using a structured questionnaire. The empirical data were analyzed using Smart-PLS software and partial least squares structural equation (PLS-SEM) model. The results of the analysis show that consumer attitudes, knowledge, perceived benefits, and perceived religious effects of Islamic banking are important determinants of bank customer interest in adopting Islamic banking services, while perceived innovation has no effect on interest in adopting Islamic banking services. The limitation of this study is that it is only limited to bank customers in Bojonegoro Regency. Future research should expand the study to various other city countries to increase the generalization of the findings of the development of Islamic banking in Indonesia.